2015
DOI: 10.1039/c5ra06409k
|View full text |Cite
|
Sign up to set email alerts
|

Superior shape memory properties and microstructure evolution of poly(ether-b-amide12) elastomer enhanced by poly(ε-caprolactone)

Abstract: In this work, the superior shape memory properties and microstructure evolution of poly (ether-b-amide12) (PEBA) enhanced by poly(3-caprolactone) (PCL) were investigated. The PEBA/PCL blends were prepared by the methods of solution mixing and compression molding. The representative phase-separated morphologies were observed by optical microscopy (OM). The recovery stress and shape memory properties of the samples were determined by dynamic mechanical analysis (DMA). It was found that high loadings of PCL (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Two rings, located at q = 1.38 nm –1 and 1.58 nm –1 , can be indexed as (020/1̅11) and (110) reflections from a monoclinic α crystal of PBS . The others, located at q = 1.51 nm –1 and 1.67 nm –1 , are related respectively to the (110) and (200) planes of the PCL orthorhombic crystal form. , Furthermore, the intensity of the diffraction peaks of one component decreases with decreasing content. Upon heating to 60 °C, PCL crystals melt and PBS crystals are left, evidenced by the remaining two rings related with the monoclinic α crystal of PBS.…”
Section: Resultsmentioning
confidence: 99%
“…Two rings, located at q = 1.38 nm –1 and 1.58 nm –1 , can be indexed as (020/1̅11) and (110) reflections from a monoclinic α crystal of PBS . The others, located at q = 1.51 nm –1 and 1.67 nm –1 , are related respectively to the (110) and (200) planes of the PCL orthorhombic crystal form. , Furthermore, the intensity of the diffraction peaks of one component decreases with decreasing content. Upon heating to 60 °C, PCL crystals melt and PBS crystals are left, evidenced by the remaining two rings related with the monoclinic α crystal of PBS.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, the shape memory property of PEBA/PCL blends and the corresponding microstructure evolution were studied. It was found that the shape recovery stress of PEBA was enhanced by the addition of PCL . Based on these results, in the current work the blends with weight ratio of PCL/PEBA 35/65 were prepared by solution mixing and the controlling phase separation dynamics were studied.…”
Section: Introductionmentioning
confidence: 83%
“…SMPs can be divided into two main categories. One is polymer networks, including covalent crosslinked or physical crosslinked semicrystalline or amorphous copolymers; the other is polymer blends and composites . Because the synthesis of SMPs may be difficult, physical blending of polymers is a convenient and effective way to prepare shape memory composites and has potential in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations